2016
DOI: 10.3389/fnhum.2016.00443
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Oscillations Prior to Speech Onset Reflect Altered Motor Networks in Adults Who Stutter

Abstract: Adults who stutter (AWS) have demonstrated atypical coordination of motor and sensory regions during speech production. Yet little is known of the speech-motor network in AWS in the brief time window preceding audible speech onset. The purpose of the current study was to characterize neural oscillations in the speech-motor network during preparation for and execution of overt speech production in AWS using magnetoencephalography (MEG). Twelve AWS and 12 age-matched controls were presented with 220 words, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 120 publications
7
77
4
2
Order By: Relevance
“…The findings were thought to reflect the transfer of timing to sensorimotor information through fluctuations in corticobasal-ganglia and thalamocortical circuits, demonstrating how basal ganglia circuits can contribute to forward models by coding changes in predictive timing of auditory information (Arnal 2012; Arnal & Giraud 2012). Stuttering-related differences in β oscillations recently have been found in children (Etchell et al, 2016) and adults (Mersov et al, 2016). Third, selection and inhibition processes modulate and stabilize sensory experience and fluid movements operate through basal ganglia circuits (Buzsaki, 2006;Klimesch et al, 2007;Okun and Lampl, 2008;Jensen and Mazaheri, 2010) and can be measured by changes in α fluctuations across motor regions (Bonstrup et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The findings were thought to reflect the transfer of timing to sensorimotor information through fluctuations in corticobasal-ganglia and thalamocortical circuits, demonstrating how basal ganglia circuits can contribute to forward models by coding changes in predictive timing of auditory information (Arnal 2012; Arnal & Giraud 2012). Stuttering-related differences in β oscillations recently have been found in children (Etchell et al, 2016) and adults (Mersov et al, 2016). Third, selection and inhibition processes modulate and stabilize sensory experience and fluid movements operate through basal ganglia circuits (Buzsaki, 2006;Klimesch et al, 2007;Okun and Lampl, 2008;Jensen and Mazaheri, 2010) and can be measured by changes in α fluctuations across motor regions (Bonstrup et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mersov et al (2016) studied brain rhythms of fluent speakers and adults who stutter using magnetoencephalography before and during cued overt reading of words in a carrier phrase. During speech preparation, a decrease of β-power (in this study: 15–25 Hz) was found in the bilateral cuneus of fluent individuals.…”
Section: Discussionmentioning
confidence: 99%
“…We analyseerden en vergeleken modulatie in neurale oscillaties tijdens spraakvoorbereiding in een group van AWS en typisch vloeiende sprekers (Mersov et al, 2016). De AWS lieten zowel sterkere bèta-onderdrukking als bèta-synchronisatie zien in de bilaterale mondmotorcortex.…”
Section: Meg Studies Van Individuele Stottermomentenunclassified